2014
DOI: 10.3791/51056
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Dissociated Intrinsic Hand Muscle Atrophy in the Diagnosis of Amyotrophic Lateral Sclerosis

Abstract: The split hand phenomenon refers to predominant wasting of thenar muscles and is an early and specific feature of amyotrophic lateral sclerosis (ALS). A novel split hand index (SI) was developed to quantify the split hand phenomenon, and its diagnostic utility was assessed in ALS patients. The split hand index was derived by dividing the product of the compound muscle action potential (CMAP) amplitude recorded over the abductor pollicis brevis and first dorsal interosseous muscles by the CMAP amplitude recorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 25 publications
(33 reference statements)
1
13
0
1
Order By: Relevance
“…Split-hand phenomenon is one important clinical feature of ALS patients, characterized by preferential wasting of the thenar muscles, while the hypothenar muscles are relatively less involved[ 21 23 ]. Our findings showing significantly increased SI in ALS, are consistent with previous studies, and suggest that split-hand is an important neurophysiological feature of ALS[ 22 , 24 – 26 ]. Since these muscles of thenar and hypothenar were innervated by the same myotomes, the difference of involvement severity of these two sites seems not be derived from spinal cord.…”
Section: Discussionsupporting
confidence: 93%
“…Split-hand phenomenon is one important clinical feature of ALS patients, characterized by preferential wasting of the thenar muscles, while the hypothenar muscles are relatively less involved[ 21 23 ]. Our findings showing significantly increased SI in ALS, are consistent with previous studies, and suggest that split-hand is an important neurophysiological feature of ALS[ 22 , 24 – 26 ]. Since these muscles of thenar and hypothenar were innervated by the same myotomes, the difference of involvement severity of these two sites seems not be derived from spinal cord.…”
Section: Discussionsupporting
confidence: 93%
“…The recently suggested electrophysiological ‘split-hand-index’, which uses the CMAP amplitude for calculation, might also be adapted for MUNIX measurements 24 25 27 28. This index additionally uses the first interosseus dorsalis muscle (FDI) 27 28. MUNIX measurements from the FDI have already been performed 18.…”
Section: Resultsmentioning
confidence: 99%
“…Wilbourn 4 first reported split hand syndrome in upper limb-onset ALS patients, which refer to Abductor pollicis brevis (APB) and first dorsal interosseous (FDI) muscles being predominantly affected by relative sparing of abductor digiti minimi (ADM). Menon P and Park D 5 further confirmed this phenomena through electrophysiology studies. They revealed that compound muscle action potentials (CMAP) of APB and FDI were significantly lower than CMAP of ADM.…”
Section: Introductionmentioning
confidence: 70%
“…They revealed that compound muscle action potentials (CMAP) of APB and FDI were significantly lower than CMAP of ADM. The results were presented as split hand index (SI, ) 5,6 .They found that the “split hand” could be used to differentiate ALS from CSA 5,7 . Recently, Neil reported dissociated lower limb muscle involvement in ALS 8 .…”
Section: Introductionmentioning
confidence: 99%